BIOGEOGRAPHIC RELATIONSHIPS OF THE GORGONA ISLAND ANTS - BAENA, MARTHA LUCÍA; ALBERICO, MICHAEL (Revista Colombiana de Entomología, 1991)
A total of 60 ant species, pertaining to six Neotropical subfamilies, were collected on Gorgona Island from October 1989 to May 1990. Many of these represent new reports for Western Colombia. The subfamily Ponerinae, having the most complete distributional database, was used for biogeographical analysis compared with the Pacific coast based on presence-absence data collected from December 1988 to May 1990. Geological data suggest that Gorgona was last connected to the South American continent approximately 17.000 years ego Ectatoma goninion Kugler & Brown (Ponerinae), the only species of this genus found in Gorgona, has els° been reported for the Pacific coast from Western Choco and Esmeraldas (Ecuador). On this basis, a new hypothesis is proposed concerning the former Andean cordillera along the Pacific coast of Colombia. This cordillera was possibly more continuous than previously proposed, linking the Serranía del Baudo with Northwestern Ecuador, permitting colonization of Gogona by two routes: From Ecuador in the south, and from the Choco in the north. This also suggests that a large river which separated Gorgona from the continent prevented the colonization of the proto-island of Gogona by species from the East. The data else permit a more detailed picture of habitat and resource. availability en the distribution of ant species.